2020
DOI: 10.1038/s41467-019-14052-x
|View full text |Cite|
|
Sign up to set email alerts
|

Divergent mutational processes distinguish hypoxic and normoxic tumours

Abstract: Many primary tumours have low levels of molecular oxygen (hypoxia), and hypoxic tumours respond poorly to therapy. Pan-cancer molecular hallmarks of tumour hypoxia remain poorly understood, with limited comprehension of its associations with specific mutational processes, non-coding driver genes and evolutionary features. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, which aggregated whole genome sequencing data from 2658 cancers across 38 tumour types, we quantify hyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 50 publications
3
72
2
1
Order By: Relevance
“…However, a recent study suggested that large number of mutations were identified in patients with hypoxic tumors with higher incidence in deletions, duplications, and single nucleotide changes. 27 The authors also identified mutational signatures from single base substitutions and frameshift mutations correlating with defective DNA repair (homologous recombination and mismatch repair), suggestive of hypoxic contribution to such genotypes. 27 An increase in insertions and deletions was observed in comparison to single nucleotide variations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a recent study suggested that large number of mutations were identified in patients with hypoxic tumors with higher incidence in deletions, duplications, and single nucleotide changes. 27 The authors also identified mutational signatures from single base substitutions and frameshift mutations correlating with defective DNA repair (homologous recombination and mismatch repair), suggestive of hypoxic contribution to such genotypes. 27 An increase in insertions and deletions was observed in comparison to single nucleotide variations.…”
Section: Discussionmentioning
confidence: 98%
“…27 The authors also identified mutational signatures from single base substitutions and frameshift mutations correlating with defective DNA repair (homologous recombination and mismatch repair), suggestive of hypoxic contribution to such genotypes. 27 An increase in insertions and deletions was observed in comparison to single nucleotide variations. Rospo and coworkers demonstrated that the incidence of insertions and deletions was much more prevalent in colorectal cancers having DNA repair defects like polymerase E mutations and high microsatellite instability.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, active immune infiltration in fTME seemed to increase hypoxia level. Recently, elevated hypoxia was also found to be associated with increased TMB across cancer types including GC ( 40 ). Because high TMB promotes immune infiltration by producing more novel peptide epitopes or neoantigens ( 41 ), this finding indicated again the association between immune infiltration and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The Supplemental Materials and the scores for intratumor hypoxia were downloaded from Bhandari et al and Buffa et. al, respectively [ 57 , 58 , 69 ]. Mann-Whitney U tests with FDR adjustment were used to compare intercohort scores [ 11 , 52 ].…”
Section: Methodsmentioning
confidence: 99%